Efficacy of incorporating PCM into the building envelope on the energy saving and AHU power usage in winter - Abu-Hamdeh, Nidal H.; Melaibari, Ammar A.; Alquthami, Thamer S.; Khoshaim, Ahmed; Öztop, Hakan Fehmi; Karimipour, Aliakbar (Elsevier, 2021)
Commercial and residential buildings consume 20% of the world's total energy usage and forecasts indicate a growing trend of 1.5% per year by 2040. Share of energy consumption in the heating ventilation and air conditioning (HVAC) reached to 40-70% of the building energy usage. Reduction in the heat exchange between the interior and exterior spaces is an energy-efficient technique for lowering HVAC energy demand. In this study, the thermal performance of a PCM-based wall was numerically examined in the winter. The main purpose of this research was to investigate the efficacy of installing PCM inside the envelope on reducing heat loss from the conditioned space and at the same time its effect on air handling unit (AHU) energy usage. For this, seven different PCM layers at melting temperatures of 276.15-293.15 K with a thickness of 1 cm were loaded into the envelope. Based on the results, among the PCMs thermophysical properties, thermal conductivity has more manifest efficacy. Under the best conditions, owing to installing PCM of A3 inside the envelope, the energy-saving in December, January and February diminished by 11.25%, 11.23% and 10.35%, respectively. Also, thermodynamic calculations affirmed that the maximum reduction in AHU power usage owing to PCM loading was 11.73%. Using payback time technique, the economic analysis was performed and it was found that under the best conditions, the payback time is 18.6 years.
Keywords: Phase change material; Envelope; Air handling unit; Energy saving; Economic analysis